Clarity and Confusion in the Development of Youth Aerobic Fitness - Armstrong, Neil; Welsman, Jo (Frontiers in Physiology, 2019)
.Peak oxygen uptake (V ̇O_2) is internationally recognized as the criterion measure of youth aerobic fitness, but flawed laboratory assessments and fallacious interpretations of peak V ̇O_2 in ratio with body mass have confused our understanding of the development of aerobic fitness. Moreover, the recent emergence of specious predictions of peak V ̇O_2 from performance tests and the promotion of spurious ‘clinical red flags’ and cardiometabolic cut-points have confused our understanding of the relationship between youth aerobic fitness and health. Recent longitudinal studies of 10-18 year-olds using multilevel allometric modelling have empirically demonstrated that peak V ̇O_2 increases in accord with sex-specific, concurrent changes in age- and maturity status-driven morphological covariates with the timing and tempo of changes specific to individuals. During both cycle ergometry and treadmill running age- and maturity-status- driven changes in fat free mass have been revealed as the most powerful morphological influences on the development of youth aerobic fitness. To bring some clarity to current confusion, this paper argues that future studies must be founded on rigorous assessment and interpretation of peak V ̇O_2 and ensure that they address the development of youth aerobic fitness and its relationship with present and future health in relation to appropriate sex-specific morphological covariates governed by individual biological clocks.